Online piety and its discontent: revisiting Islamic anxieties on Indonesian social media. Issue 134 (2nd January 2018) - Husein, Fatimah; Slama, Martin
ABSTRACT: In today's digital age, many Indonesian Muslims utilise social media, such as Facebook, WhatsApp and BlackBerry Messenger (BBM), to express their piety. However, their religious online practices are not devoid of ambiguities, discontents and tensions. The article focuses on these specific consequences of being digitally pious in Indonesia. It examines how riyā', an established concept in Islamic theology that refers to showing off one's piety, has gained new relevance in the context of contemporary uses of social media for religious purposes. The article particularly discusses online Qur'an reading groups (ODOJ) and sedekah (charity) activities that utilise social media, and asks how Muslims deal with the problem of riyā', which is strongly discouraged in Islamic theology, and with the discontent and anxieties it generates. At the same time, it reveals that the responses to the challenge that riyā' poses vary greatly and that Indonesian Muslims have found different ways to overcome it.